Institutional trading and Abel Noser data - Hu, Gang; Jo, Koren M.; Wang, Yi Alex; Xie, Jing (Journal of Corporate Finance, 2018)
We survey the growing academic literature using Abel Noser data, including 55 publications thus far. We analyze publication patterns to explore how the availability of a specialized microstructure dataset propagates across different areas within finance and into other disciplines such as accounting. Of note, we identify corporate finance and accounting as the most under-researched areas that offer promising opportunities for future academic research using the data. To provide guidance for researchers interested in using Abel Noser data, we analyze institutional trading using transaction-level data spanning more than 12 years and covering 233 million transactions with $37 trillion traded. We provide background information on the origin and history of the data, offer suggestions for cleaning and using the data, and discuss (dis)advantages of Abel Noser compared to other data sources for institutional trading. We also document two simple facts: 1) institutional trade sizes decline dramatically over time, rendering trade size-based inferences of institutional trades problematic; 2) we estimate that Abel Noser data cover 12% of CRSP volume over our sample period and 15% for 1999–2005, significantly higher than the estimate in Puckett and Yan (2011) for 1999–2005: 8%, a widely quoted number in the literature. This background should prove useful for researchers seeking to address a number of as yet unexplored issues, especially in corporate finance and accounting research.